Love it, change it, or leave it: Understanding highly-skilled flexible workers' job satisfaction from a psychological contract perspective - Uta Wilkens; Daniel Nermerich (Management Revue, 2011)
In order to understand highly-skilled flexible workers' job satisfaction, we take their track records into consideration, integrating several employment contracts. We conceptualize our research interest within the framework of the psychological contract to explore individual rationalities in exchange relationships. This expectancy-oriented approach allows the reflection of contract arrangements and related attitudes from a process perspective. The analysis is based on a qualitative approach, investigating data from 13 indepth interviews with workers from knowledge-intensive working contexts. As a result, it becomes evident that an inherent notion of continuity independent of the formal work contract exists, job episodes apparently indicate continuity. For the interviewees, pro-active changes in episodic work relationships are a dominant coping pattern for sustaining satisfaction at a high aspiration level. Satisfaction appears as an interactional construct with a high notion of reciprocity, acknowledgment and skill development. The emphasis on career track satisfaction instead of job satisfaction and the specification of dynamics across several job episodes as an external regulation for keeping satisfaction at a high aspiration level provides new insights in research on job satisfaction.
Keywords: D23; J28; J24; 650; job satisfaction; aspiration level; flexible employment; new employment relationship; psychological contract; reciprocity